Implementación de un modelo didáctico para el curso de capacitación de control de pozo para las operaciones de perforación y acondicionamiento del pozo (2017)
The present project has the purpose of implementing a didactic model for the well control training course for well drilling and conditioning operations, through a description of the material used in the training of the new levels of WellSharp certification of the IADC (International Association of Drilling Contractors), it was established that it is intended to reinforce knowledge, advances in practices and procedures among other resources relevant to the development of the material.